Compositions of fuzzy relations applied to veryfication learning outcomes on the example of the major “Geodesy and Cartography” - Mreła, A.; Sokolov, O. (Journal of Education, Health and Sport, 2015)
Mreła A., Sokołov O. Compositions of fuzzy relations applied to veryfication learning outcomes on the example of the major “Geodesy and Cartography”. Journal of Education, Health and Sport. 2015;5(5):183-192. ISSN 2391-8306. DOI 10.5281/zenodo.17495 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A183-192 https://pbn.nauka.gov.pl/works/559399 http://dx.doi.org/10.5281/zenodo.17495 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. COMPOSITIONS OF FUZZY RELATIONS APPLIED TO VERYFICATION LEARNING OUTCOMES ON THE EXAMPLE OF THE MAJOR “GEODESY AND CARTOGRAPHY” A. Mreła, O. Sokołov A. Mreła, Kujawsko-Pomorska Szkoła Wyższa w Bydgoszczy Polska, 85-023 Bydgoszcz, ul. Toruńska 55-57 E-mail: a.mrela@kpsw.edu.pl O. Sokołov, Uniwersytet Mikołaja Kopernika w Toruniu Polska, 88-100 Toruń, ul Gagarina 11 E-mail: o.sokolov@umk.pl Abstract The paper presents discussion about using mathematical functions in order to help academic teachers to verify acquirement of learning outcomes by students on the example of the major “geodesy and cartography”. It is relatively easy to build fuzzy relation describing levels of realization and validation learning outcomes during subject examinations and the fuzzy relation with students’ grades is already built by teachers, the problem is to combine these two relations to get one which describes the level of acquiring learning outcomes by students. There are two main requirements facing this combinations and the paper shows that the best combination according to these requirements is algebraic composition. Keywords: learning outcome, fuzzy relation, algebraic composition.